Penapisan Aktivitas Selulase Isolat-isolat Khamir dari Moluska, Serasah, dan Tumbuhan di Taman Nasional Gunung Halimun, Jawa Barat - Mangunwardoyo, Wibowo; Fitri, Reno; Oetari, Ariyanti (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
A total of 236 yeast isolates from mollusc, litter, and plant samples from Gunung Halimun National Park were screened for cellulolytic activity based on Smith method by using 0,2% (w/v) cellulose-azure for 30 days. The results showed that 12 isolates (9 isolates from plants, 2 isolates from molluscs, dan 1 isolate from litter) have cellulolytic activity. These isolates were further screened based on Teather and Wood method for six days to determine their cellulases components by using specific substrates. Carboxymethyl cellulose (CMC) 0,1% (w/v) was used as a specific substrate to determine endoglucanase activity. Avicel 0,1% (w/v) was used as a specific substrate to determine exoglucanase activity. Cellobiose 0,1% (w/v) was used as a specific substrate to determine Î²-glucosidase activity. The results showed that 6 isolates from plant have Î²-glucosidase activity, and 1 isolate from plant have Î²-glucosidase and endoglucanase activities. Five isolates (2 isolates from plants, 2 isolates from molluscs, and 1 isolate from litter) showed no cellulase activity on specific substrates after six days incubation.